Teacher Retention in Rural Indonesian Schools: An Interpretative Phenomenological Analysis of Career Disorientation and Commitment - Liris Raspatiningrum; Siti Rubai’ah; Rizki Satria Nugraha; Rifan Shodikin; Richard Lionel Gorni (Journal of Education and Teaching (JET), 2025)
In Indonesia, the chronic imbalance in teacher distribution—particularly the scarcity and attrition of educators in rural regions—has emerged as a national crisis that threatens educational equity and long-term system sustainability. This study aims to explore the lived experiences of teacher career development and retention in rural Indonesian schools using an interpretative phenomenological approach. Data were collected through in-depth, semi-structured interviews with 18 participants, including elementary and secondary school teachers with 5–25 years of teaching experience, drawn from diverse rural provinces such as West Java, Central Sulawesi, and East Nusa Tenggara. The analysis was conducted through iterative coding and meaning-making cycles following the Interpretative Phenomenological Analysis (IPA) framework proposed by Smith et al. (2009), which facilitated the extraction of emergent themes and contextual insights. Six interrelated themes were identified: career path disorientation, lack of developmental support, professional alienation, delayed milestones, moral commitment, and systemic imbalance. Despite persistent structural adversities, many educators remain committed due to ethical loyalty and a sense of community responsibility. The study concludes that retention strategies must incorporate culturally grounded, participatory, and context-sensitive frameworks.